(untitled) (PANGEEA, 2025)
Romania’s healthcare system faces persistent regional disparities, shaped by historical governance structures, economic inequalities, and systemic inefficiencies. This study analyzes the evolution of healthcare facilities across development regions during two key periods: before European Union (EU) integration in 2007 and after 2017. Using statistical data from Eurostat, the National Institute of Statistics (INS), and other sources, the article presents a detailed comparison of healthcare infrastructure across regions. The findings reveal persistent inequalities, despite modernization efforts driven by EU funding. The study highlights critical areas for policy intervention to address these disparities and promote equitable healthcare access.